EFEKTIVITAS PROGRAM QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) DALAM MENINGKATKAN AKUNTABILITAS PENGELOLAAN DANA PUNIA PADA PURA DANG KHAYANGAN PETITENGET - Lyani, Ade; Wismayanti, Kadek Wiwin Dwi; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2023)
The implementation of the Quick Responses Code Indonesian Standard (QRIS) program in punia funds at Pura Dang Khayangan Petitenget has an important role in helping transparency and accountability in financial management of punia funds. The results showed that the implementation of the QRIS program in donating punia at Pura Petitenget was running quite well but not yet fully running optimally. There are several obstacles that occur in the program socialization indicators, where the BPD Bali is still not optimal in socializing the use of QRIS in donations, there are still people who don’t know the QRIS program for punia funds so they prefer cash payments, lack of education for temple managers about the QRIS program, and also the temple management is still not cooperative with the placement of the QRIS logo. Obstacles also occur in program monitoring indicators, namely there are still frequent signal disturbances when accessing QRIS at temples Keywords: Program Effectiveness, Quick Response Code Indonesia Standard (QRIS), Accountability, Punia Funds.